2014
DOI: 10.1007/s13277-014-2350-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs as novel biomarkers for detecting esophageal squamous cell carcinoma in Asians: a meta-analysis

Abstract: Accumulating evidence has suggested that microRNAs (miRNAs) may play potential role as ideal diagnostic indicators of esophageal squamous cell carcinoma (ESCC). However, previous studies have met discrepant results. Thus, we conducted this meta-analysis to assess the potential diagnostic value of miRNAs for ESCC. A systematic literature search was conducted in PubMed and other databases. The pooled sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…27 Our present meta-analysis also showed the similar results and verified that blood miRNAs had a relatively high diagnostic accuracy. More importantly, the advantages of our meta-analysis are as follows: first, this study was much larger, with more than twice as many studies as the earlier meta-analysis.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…27 Our present meta-analysis also showed the similar results and verified that blood miRNAs had a relatively high diagnostic accuracy. More importantly, the advantages of our meta-analysis are as follows: first, this study was much larger, with more than twice as many studies as the earlier meta-analysis.…”
Section: Discussionsupporting
confidence: 85%
“…50,51 This pooled method is different from a previous meta-analysis of circulating miRNAs in the diagnosis of ESCC, which treated the discovery and validation groups as one single group. 27 If these two groups are not independent, sum of samples size may lead to a population overlapping bias. Our combined studies approach should increase the accuracy statistics from the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Wang et al[45] of eight manuscripts investigated a total of 16 different types of miRNAs in serum and saliva of Asian esophageal squamous cell carcinoma patients. The authors reported relatively high sensitivity and specificity values for combination and single miRNA markers, suggesting some diagnostic application[45].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…The authors reported relatively high sensitivity and specificity values for combination and single miRNA markers, suggesting some diagnostic application[45]. The prognostic utility of miRNAs have also been reviewed, with Fu et al[46] reporting on 39 potentially prognostic miRNAs in 25 individual studies.…”
Section: Circulating Mirnamentioning
confidence: 99%